GAZPROM AS A TRANSNATIONAL CORPORATION AND CENTRAL ASIA Part One - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2006)
Russia occupies third place in terms of world oil supplies: it accounts for approximately 10% of the world reserves, or 27% of the oil supplies outside OPEC. In terms of oil pro duction, the Russian Federation is on a par with Saudi Arabia, the world leader, and in terms of oil export volumes, it is securely in second place. Russia is the absolute leader in the gas sector: it accounts for approximately one third of the world’s total reserves, one quarter of world production, and approximately 30% of world export, while its main gas transportation system has no analogies in terms of length and complexity.The unprecedented trends on the oil markets are having a decisive influence on the nature and rates of Russia’s economic growth: oil and gas export is responsible for more than one third of the revenue going into the state treasury. In 2004, the Russian Federation accounted for 10.97% of the entire world oil production. According to the forecasts of the country’s government, the export of Russian oil will reach 253 million tons in 2006 and 260 million in 2007.As a major fuel and electric energy exporter, on the deliveries of which the economy of several neighboring countries largely depends, Russia has a good opportunity to strengthen its own economic and political positions.The main feature of Russia’s foreign policy lies in the fact that Moscow is using the economy (to be more precise, energy cooperation) as a powerful tool to reach its foreign policy goals. This concerns both Russia’s relations with the West and with Asian countries (China and Japan). But Russia’s energy strategy is making itself known to an even greater extent in relations with the CIS countries. This factor—energy policy as a geopolitical tool—directly affects the national, economic, and energy interests of the Central Asian countries.Russia’s energy geostrategy is evolving in three main areas: Western Europe, Central Asia, and the Far East. The European vector is the central one, since it is ensuring the main inflow of revenues and forms the foundation of Russia’s economic relations with the EU, giving Moscow geopolitical clout and international influence.